Captain Underpants and the terrifying return of Tippy Tinkletrousers : the ninth epic novel - Pilkey, Dav, 1966- (New York : Scholastic, 2012)
After being sent to jail for the rest of their lives, George and Harold are taken on a trip back in time by Tippy Tinkletrousers back to their Kindergarten days where they must deal with their bully without the help of Captain Underpants.
Pub Weekly, July 2012.
5.1
3-6
850L
Keywords: Captain Underpants (Fictitious character) -- Juvenile fiction; Time travel -- Juvenile fiction; Bullying -- Juvenile fiction; Schools -- Juvenile fiction; Heroes -- Juvenile fiction; Captain Underpants (Fictitious character) -- Fiction; Time travel -- Fiction; Bullies -- Fiction; Schools -- Fiction; Heroes -- Fiction; Humorous stories; Captain Underpants (Fictional character) -- Fiction; Time travel -- Fiction; Bullies -- Fiction; School stories; Heroes and heroines -- Fiction; Humorous fiction; Time travel -- Fiction; Schools -- Fiction; School principals -- Fiction; Superheroes -- Fiction; Humorous stories; Humorous fiction